MATHEMATICAL MODELING AND SCENARIOS FOR INVESTIGATION: THE DEVELOPMENT OF A CRITICAL STANCE TOWARDS THE SOCIAL REALITIES OF STUDENTS - Nomura, Joelma Iamac (Seven Editora, 2025)
This paper aims to present the contribution of Mathematical Modeling to the construction of different Scenarios for Investigation in the teaching and learning of Mathematics in higher education courses. The search for different Scenarios for Investigation can stimulate student engagement through activities that encourage their connection with real-life situations and their professional experiences. Thus, we highlight the guiding question of this research: What are the contributions of Mathematical Modeling in the construction of different Scenarios for Investigation in higher education? According to our studies, we found different scenarios constructed according to different mathematical entities and with a high degree of reference to real life. It is worth noting that, in all the situations studied, we considered the interdisciplinary aspect between mathematical objects, undergraduate programs, and, above all, how this aspect presents itself in relation to the possible professional roles of future graduates. To support the definition of different Investigation Scenarios, we base ourselves on the theoretical assumptions of Skovsmose (2000) and Alro and Skovsmose (2010), in addition to the main ideas adopted by Bassanezi (2010) and Biembengut and Hein (2000) regarding teaching and learning with Mathematical Modeling. To this end, we rely on academic works selected from CAPES databases that considered the teaching and learning of mathematical objects in relation to the construction and analysis of models. In this sense, we adopted an investigative stance based on documentary research in a qualitative approach. Among the research analyzed, we highlight Investigation Scenario 1, portrayed in this work, which evidences the construction of a Mathematical Model for studying the lifespan of an overpass as a function of local vehicle flow. The constructed model pointed to mathematical arguments that support the group's estimates, and its analysis was supported by the students' critical stances on the well-being of the population and the use of public funds. We consider that mathematical models encourage learning based on different Scenarios for Investigation, such as those related to social functions or other problems existing outside the educational universe that are close to the students' experiences.DOI: https://doi.org/10.56238/sevened2025.038-057